Schumpeterian Democracy and the Winnability of Barisan Nasional : Voting Behavior and Political Markets Distortions in Malaysia - Mohd. Kamal, K.A. (Universiti Malaysia Sarawak, 2011)
Barisan Nasional (and its predecessor Perikatan) has won all Federal Elections and most of the state elections since the Independence of Malaya and the formation of Malaysia. Why is this so? In this paper I conceptualize possible reasons why BN won. I begin with Newman and Sheth’s (1985) static model of primary voting behavior and then adapt this model to fit into the Malaysian context, in particular by identifying distortions in the markets of information and impediments in the market of political positions. More importantly, I will incorporate the dynamic major political processes outside of elections into that model, whilst seeing the voter to be the consumer of public services from political markets. From this model, the tentative conclusion of the winnability of BN lies in its ability to distort the markets of information, besides being able to impede the political markets. However, due to changes, this explanation cannot be sustained; I therefore suggest a new way of thinking about voting behavior in Malaysia that puts the voter as the central component.